Health and physical well-being during primary school age - Altavilla, Gaetano (Formazione & insegnamento, 2023)
WHO recommends that individuals spend at least 60 minutes a day in moderate to vigorous intensity physical activity (MVPA). Especially for children, physical activity (PA) stands as a tool for promoting adequate motor, cognitive and social development. In Italy, the National Directions enshrine for PA in school the guidelines to be pursued to ensure the proper development of the student. However, despite the increasing interest of international and national organizations, while in most of the world there has been a significant development in the quality of the tools to be used within schools, in Italy there has been a stalemate. The aim of the review is to highlight the important value that PA holds in health promotion in the 5–11 age group, in order to urge more concrete action for the promotion of PA in Italian schools. The method used is that of review through consultation of web search engines.